2001
DOI: 10.1590/s0100-41582001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de bioprotetores em patógenos de sementes e na emergência e rendimento de grãos de milho

Abstract: Um experimento de laboratório e dois de campo, conduzidos nas localidades de Passo Fundo, RS, e Pato Branco, PR, foram realizados com o objetivo de avaliar os efeitos da microbiolização de sementes sobre os patógenos de sementes e sobre a germinação e rendimento de grãos de milho (Zea mays). Em laboratório, a maioria dos bioprotetores reduziu significativamente o nível de patógenos de sementes. Nos experimentos de campo, no ano de 1997, em Passo Fundo, RS, somente Trichoderma harzianum (T-22) melhorou signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
4
0
10
Order By: Relevance
“…The result afore mentioned can be explained by the fact that seeds remained for 24 hours in the freezer, affecting B. subtilis cells. Different results were found by Angonese et al (2009), in which Bacillus genus bacteria showed great potential to be used as phytopathogenic fungi biological control agents, significantly reducing Fusarium graminearum and Stenocarpella maydis infection in maize seeds (Luz, 2001) and fungi incidence in soybean seeds (Bezerra et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The result afore mentioned can be explained by the fact that seeds remained for 24 hours in the freezer, affecting B. subtilis cells. Different results were found by Angonese et al (2009), in which Bacillus genus bacteria showed great potential to be used as phytopathogenic fungi biological control agents, significantly reducing Fusarium graminearum and Stenocarpella maydis infection in maize seeds (Luz, 2001) and fungi incidence in soybean seeds (Bezerra et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
“…Luz (2001) and Resende (2003) also observed significant seedling emergence increase in maize seeds treated with T. harzianum.…”
Section: Resultsmentioning
confidence: 88%
“…Other authors had verified strains of Trichoderma spp. increasing the percentage of germination of other grasses, such as maize and black oats (Luz, 2001;Shoresh et al, 2010;Machado, 2011). As for organomineral fertilizer, Aguiar et al (2009) found an increase in the number of mitoses and lateral roots of grass seedlings, such as maize, suggesting that humic substances may accelerate the seed germination process.…”
Section: Discussionmentioning
confidence: 99%
“…Grandes culturas como o feijoeiro comum (Bernardes et al, 2010;Carvalho et al, 2011), girassol (Guareschi et al, 2012), milho (Luz, 2001) e soja (Mertz et al, 2009;Guareschi et al, 2012) (Amaral et al, 2017). A combinação de espécies de Trichoderma com outros compostos que possam melhorar sua aderência às sementes também pode ser considerado interessante.…”
Section: Introductionunclassified